Endometrial cancer prognosis prediction using correlation models based on CDK family genes - Gu, Xianhua; Shen, Honghong; Bai, Wenqi; Xiang, Zheng; Li, Xinwei; Zhang, Rong; Shi, Fan; Li, Huiyuan; Zhu, Guangzheng; Guo, Suyang (Frontiers in Genetics, 2022)
Cyclin-dependent kinases (CDKs) play an important role in cell division. Given that abnormal cell proliferation caused by dysregulation of cell division is one of the major causes of endometrial cancer (EC), it is important to elucidate the role of CDK family genes in the diagnosis and prognosis of EC. In this study, The Cancer Genome Atlas (TCGA) database was used to analyze the frequency of copy number variations and somatic mutations in 26 CDK family genes. Subsequently, the expression of these genes in EC was assessed, and their relationship with overall survival (OS) was examined via Kaplan–Meier analysis to assess their prognostic significance. A prognostic model based on seven CDK genes was constructed using Lasso and Cox regression, and the predictive performance of the model was analyzed using Kaplan–Meier analysis and column line plots. The correlation between CDK genes and immune cells was also examined. Patients with EC in the high-risk group had a poorer prognosis. The results of qRT-PCR and immunohistochemical analyses validated that CDK16 is highly expressed in EC tissues. Patients with EC with high CDK16 expression had worse 10-year OS than patients with low CDK16 expression. These findings suggest that the prognostic model constructed based on CDK genes can help to develop individualized and targeted treatment strategies for patients with EC.